Exam reform: an opportunity for the redistribution of academic power - Gregory J. Crowther; Benjamin L. Wiggins (Journal of Microbiology & Biology Education)
ABSTRACT Students in STEM know well the stress, challenge, and effort that accompany college exams. As a widely recognizable feature of the STEM classroom experience, high-stakes assessments serve as crucial cultural gateways in shaping both preparation and motivation for careers. In this essay, we identify and discuss issues of power around STEM exams to further the understanding of exam practices that can unjustly hold students back. Through theory and practical examples, we consider the numerous ways in which power manifests both on and off the pages of the exams themselves, as well as ways in which power is consolidated away from students through logistical norms and tradeoffs. Centering the “rules of the culture of power” as delineated by Dr. Lisa Delpit, we reflect on exam practices that prioritize faculty voice and faculty convenience above student learning and student identity. We share some of what we have learned from our students as part of a call to improve STEM education by relinquishing some of our exam-related power over students, redistributing it to students so that they have more power to shape their own education.